2014
DOI: 10.1186/s13012-014-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Practice change toward better adherence to evidence-based treatment of early dental decay in the National Dental PBRN

Abstract: BackgroundSignificant national investments have aided the development of practice-based research networks (PBRNs) in both medicine and dentistry. Little evidence has examined the translational impact of these efforts and whether PBRN involvement corresponds to better adoption of best available evidence. This study addresses that gap in knowledge and examines changes in early dental decay among PBRN participants and non-participants with access to the same evidence-based guideline. This study examines the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…30 Indeed, clinician participation in dental PBRNs has helped the implementation of clinical scientific evidence into everyday patient care. 313233 …”
Section: Discussionmentioning
confidence: 99%
“…30 Indeed, clinician participation in dental PBRNs has helped the implementation of clinical scientific evidence into everyday patient care. 313233 …”
Section: Discussionmentioning
confidence: 99%
“…4 In the last decade, electronic dental record (EDR) data have been increasingly used for clinical research and quality improvement purposes in academic settings and larger health care systems. [5][6][7][8][9][10] Studies in Europe and Canada have also utilized longitudinal data from solo and group practices to assess treatment outcomes, such as longevity of composite versus amalgam restorations. [11][12][13][14] These authors highlighted the need for more studies from practice-based contexts to study more-diverse patient cohorts and restorative procedures not performed in well-controlled randomized controlled trials.…”
Section: Background and Significancementioning
confidence: 99%
“…A patients' DOB was assessed as incorrect if the patients' calculated age was less than 0 years or greater than 100 years. A tooth number was considered incorrect if it was outside the range 1 to 32, or tooth numbers were represented as tooth ranges (e.g., [2][3][4][5][6][7][8]. Observations that represented tooth surfaces other than facial (F), buccal (B), mesial (M), distal (D), lingual (L), and occlusal (O) were considered incorrect.…”
Section: Data Quality Assessmentmentioning
confidence: 99%
“…The improvement was toward using more prevention to treat dental caries and delaying the surgical treatment process in certain instances, according to the latest evidence-based research results. 48,49 We learned that a highly interactive meeting with fellow practitioner-investigators could be an effective mean to apply scientific findings into clinical practice, as clinicians reported that they would change how they treat patients as a result of being engaged in the scientific process. This “change in intention” is consistent with the health change theory, which suggests that this step is a prelude to the subsequent next step, which is the actual implementation of change in the practice.…”
Section: Paradigm Shiftmentioning
confidence: 99%